User perception on interactive digital exhibits and learning experience - Abu Bakar, Juliana Aida; Mahmud, Murni; Jahn Kassim, Puteri Shireen (IEEE, 2015)
This study aims to investigate visitor perception on the interactive digital exhibits (IDE) for learning cultural heritage and history. It further identifies possible ways IDE may help in order to improve visitor learning experience during their visit to historical and cultural heritage institutions. Four related institutions were selected in this study: Taman Tamadun Islam (TTI) and Architectural Museum Malaysia (AMM) which display architectural wonders of past civilizations by means of large replicas; as well as National Museum (NM) and Museum of History and Ethnography (MHE) which are dedicated to safeguarding and preserving the national heritage and history. TTI and NM have adequate general information technology infrastructure and digital exhibits are installed in their exhibition halls. AMM and MHE have less digital exhibits and most exhibits consist of a mixture of posters, artefacts, and replica. During this study, a survey was conducted by means of interview with 311 respondents who are also visitors to these four institutions. The findings of this study suggest most visitors perceived the use of IDE in general will allow easy access to information on national history and cultural heritage. They recommended IDE to be used as interpretation methods in order to make national history and cultural heritage more attractive. Interestingly, when it comes to available exhibition techniques, visitors vary their preferences on IDE over traditional means of exhibits according to the nature of these institutions. These findings reflect that museum visitors welcome the use of IDE and nevertheless appreciate the aesthetic values of real artefacts.